Co-infection with Proteus mirabilis and extraintestinal pathogenic Escherichia coli aggravated liver injury in chickens by disrupting the jejunal barrier - Jin-qi Cen; Zhe Yang; Xiao-li Liu; Nan-lin Wang; Si-yi Wu; Li Min; Nan Zhang; Yuanyuan Zhou; JingJing Wang; Zhongjia Yu (Poultry Science, 2025)
Avian pathogenic Escherichia coli (APEC), belong to extraintestinal pathogenic E. coli (ExPEC), causes colibacillosis in poultry, characterized by fibrinous inflammation of internal organs, high morbidity and mortality, economic losses, and food safety concerns. Proteus mirabilis is frequently isolated alongside APEC from diseased chickens, yet its role in colibacillosis remains unclear. As the intestinal lumen serves as a reservoir for both E. coli and P. mirabilis, it is possible that APEC triggers colibacillosis from the intestines, though this pathway has not been extensively studied. The present study orally gavaged chickens with an ExPEC strain with limited adhesion capacity and P. mirabilis to assess their combined impact on host health and explore potential pathogenesis. Co-inoculation resulted in significantly slower body weight gain compared to the control and single bacterial inoculation groups. Histological analysis revealed more severe liver damage in the co-inoculated group, including disordered hepatic cords, swollen hepatic cells and fatty degeneration, while only mild swelling was observed in the E. coli group. Elevated levels of inflammatory cytokines, including IL-1β and IL-18, were found in the liver, with the co-inoculated group showing the highest expression. In the jejunum, E. coli alone decreased villus length and crypt depth, while P. mirabilis impaired the villus, promoting goblet cell proliferation and reducing mucin 2 expression in both single- and co-inoculated groups. In addition to mucosal barrier disruption, increased mRNA expression of inflammatory cytokines and NF-κB in the jejunum further supported the role of P. mirabilis in intestinal inflammation. Microbial analysis using full-length 16S rRNA sequencing revealed dysbiosis, with metabolic changes induced by E. coli and resistance alterations driven by P. mirabilis. Gene expression analysis in the jejunum reflected the distinct pathogenicity of E. coli and P. mirabilis: the former altered host metabolic pathways, while the latter activated immune responses. These findings highlight the exacerbating role of co-infection with P. mirabilis and E. coli, contributing to both liver injury and intestinal disruption. Further studies are needed to elucidate the molecular pathways involved.